Diversity of freshwater red algae at Khao Luang National Park, southern Thailand - Chankaew, W.; Sakset, A.; Chankaew, S.; Ganesan, E. K.; Necchi Jr, Orlando [UNESP]; West, John A. (Korean Soc Phycology, 2019)
Freshwater red algal diversity and the relationship with water conditions in 22 stream segments in the area around Khao Luang National Park, Nakhon Si Thammarat province, southern Thailand, were studied during a period of twelve months (May 2014 to April 2015). Sixteen species of freshwater red algae, belonging to eight genera (Audouinella, Balliopsis, Batrachospermum, Caloglossa, Cornpsopogon, Kumanoa, Sirodotia, and Thorea) were identified, which were all reported earlier for the country. Thorea clavata (Thoreaceae) was the most common species occurring in eight stream segments. Caloglossa beccarii sensu lato (llelesseriaceae) and Sirodotia huillensis Skuja (Batrachospermaccae) had the highest percent cover with up to 40% and 20% per stream segment, respectively. The water quality showed most sites to be unpolluted or ultra-oligotrophic to oligotrophic. Canonical Correspondence Analysis revealed some trends in occurrence of individual species with stream environmental variables: Batrachosperrnum sp. with strong current velocity; Kumanoa hirosei with high turbidity, total dissolved solid and alkalinity; Caloglossa beccarii with high conductivity; Kumanoa tabagatenensis with high ammonia-nitrogen and Thorea siamensis with high calcium and magnesium. In view of the scarce studies on the stream ecology of freshwater red algae in Philippines and neighbouring countries, it is expected that the data presented here would be helpful in more critical further studies in south-east Asia in general.
Keywords: Audouinella; Balliopsis; Batrachospermum; biodiversity; Caloglossa; Compsopogon; environmental factors; Kumanoa; Sirodotia; Thorea